The Effect of the Internal Audit and Firm Performance: A proposed Research Framework - Ebrahim Mohammed Al-Matari; Abdullah Al-Swidi; Faudziah Hanim Binti Fadzil (International Review of Management and Marketing, 2013)
This study attempts to propose a structure of the relationships between the internal audits characteristics (IAC); such as professional qualifications of the chief audit executive of the Internal Audit (IA), size, experience, and qualification; and firm performance. The presence of an internal audit department is significant as it is considered as the main element in employing accounting systems and this, in turn, assists in evaluating the department’s work. The internal audit is deemed as the core of business accounting as it is the section that keeps track of all businesses associated with the sector. The internal audit efficiency assists in developing the company’s work because the financial reports present the internal audit department’s quality. In addition, an internal audit is a crucial part of corporate governance structure in an organization and  corporate governance (CG) covers the activities of oversight conducted by the board of directors and audit committees to ensure credible financial reporting process (Public Oversight Board, 1994). Consistent with previous studies of the importance of internal audit, this study provides comprehensive oversights on the relationship between internal audit and firm performance. The past literature reveals there is a paucity of studies exploring the association between internal audit characteristics (IAC) and firm performance whether conceptual or empirical. The main objective of this study is to fill up the gap in the literature and provide an opportunity for future research to deeply to investigate this relationship.